Surveillance of hepatocellular carcinoma (HCC) patients using Protein Induced by Vitamin K (PIVKA-II): A cost-utility analysis for Hong Kong - Man-Fung Yuen; David Wastlund; Tammie Tan Yan Lin; Qishi Zheng; Junqiao Chen; Kwan-Lung Ko (PLoS ONE, 2026)
Background & Aims Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death in Hong Kong. Common risk factors include chronic hepatitis B (CHB) infection and/ or liver cirrhosis (LC). Routine HCC surveillance using ultrasound plus alpha-fetoprotein (AFP) for patients with these conditions is recommended, but many patients still face limited access to ultrasound. For these, biomarker-based surveillance using a combination of protein induced by vitamin K absence or antagonist-II (PIVKA-II) plus AFP could provide a valuable alternative. Methods This study compared the cost-utility of routine HCC surveillance using ‘PIVKA-II + AFP’ to the recommended standard-of-care in Hong Kong: surveillance using ‘US + AFP’. A health economic model using a Markov-microsimulation framework was adapted using published local data and settings. The model was used to compare diagnostic outcomes, overall costs, quality-adjusted life years (QALYs), and cost-utility of the alternative HCC surveillance methods. Results Compared to the current recommended standard-of-care, the results suggested that HCC surveillance using ‘PIVKA-II + AFP’ could improve detection of HCC during early-stage disease by 4.6 percentage points, thus enabling access to more effective treatment options for some patients. It could also reduce false positive diagnoses by 7.2%, which could alleviate the need for costly confirmatory testing. Overall, PIVKA-II + AFP’ was associated with a gain of 0.019 QALYs and cost savings of HK $ 4,144 per individual. The results were particularly favorable for non-cirrhotic CHB patients. Conclusions HCC surveillance using ‘PIVKA-II + AFP’ could be a feasible option for patients with CHB and/ or LC who face limited access to ultrasound-based surveillance. The combination has the potential to improve early-stage HCC detection, facilitating timely intervention and improving both survival outcomes and patient quality of life.